POLICE INTEGRITY: A THEMATIC REVIEW OF ITS PUBLIC PERCEPTION - Shahriza Ilyana Ramli; Nadhrah A. Kadir; Premalatha Karupiah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Police integrity is a never ending problem discussed by scholars in all time. It involves many issues that will not only affecting government but the public in general as well. Despite its popularity, there is a little review paper has been done discussing the public perception on police integrity. This review was motivated by the belief that police integrity in a massive pedagogy that needs to scrutinize perspective of its context. Therefore, the goal of this systematic review is to synthesize literature from 2017 to 2021 on the context of police integrity using ATLAS.ti 9. A keyword search, followed by a filter using inclusion criteria from Scopus, Science Direct and Wiley Online Library databases, identified 103 peer-reviewed journal articles. However, after the inclusion and exclusion process, only 37 articles were used as the final articles to be reviewed. A thematic review of these 37 articles identified 2 initial codes characterizing police integrity issues and which later grouped them into 6 clusters: Firstly, public trust and public perception on police which influence by media, ethnicity, and personal experiences, secondly, the police misconduct issues which contributed by 3 clusters: police corruption, unwillingness of reporting which is also known as code of silence and the pressure given by peers as well as the organization. The results benefit the future study on police integrity and can be a guideline for enhancing police integrity and reducing police misconduct. , , , , ,